2015
DOI: 10.1007/s00228-015-1962-4
|View full text |Cite
|
Sign up to set email alerts
|

Off-label and unlicensed drug treatments in Neonatal Intensive Care Units: an Italian multicentre study

Abstract: Our results confirm the high prevalence of off-label/unlicensed drug use in the neonatal population and underline a better adherence to indications based on clinical practice, suggesting the need to update information contained in the data sheets of medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 36 publications
10
53
0
5
Order By: Relevance
“…and Neubert et al . who also found that anti‐infective drugs were the largest ATC class prescribed with a proportion off‐label in relation to neonatal age of 24% and 11%, respectively . For nervous system drugs, these studies found a proportion of 67% and 56% of off‐label prescriptions in relation to neonatal age, which is comparable with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…and Neubert et al . who also found that anti‐infective drugs were the largest ATC class prescribed with a proportion off‐label in relation to neonatal age of 24% and 11%, respectively . For nervous system drugs, these studies found a proportion of 67% and 56% of off‐label prescriptions in relation to neonatal age, which is comparable with our results.…”
Section: Discussionsupporting
confidence: 91%
“…with 35% in the USA , and Cuzzolin et al . with 34% in Italy . A comforting finding was that the proportion of off‐label prescriptions in relation to neonatal age increased with PMA at start of drug therapy.…”
Section: Discussionmentioning
confidence: 98%
“…As regards antibiotic choice, our findings are comparable to other Italian NICUs [3, 13], but differ from other Countries [10, 11, 14, 15]. Inter-Country and inter-centre variability in antibiotic choice, dose regimen and intervals in NICUs is commonly reported worldwide [1618] and a number of factors may explain this difference: (a) the lack of clinical trials performed in this population resulted in deficiency of international guidelines, (b) clinician’s attitude and hospital policy may also play an important role in both the choice of active substances and the pattern of antibiotic use, (c) moreover, the local epidemiology of bacterial infection is an essential factor, as well as previous maternal infections.…”
Section: Discussionsupporting
confidence: 85%
“…This IRB exempt study took place from October 2017 to December 2017. An English language, cross‐sectional survey was developed by conducting a benchmarking literature review on neonatal DI . The survey contained three sections: demographics, guideline content/DI references, and accessibility and maintenance of guidelines.…”
Section: Methodsmentioning
confidence: 99%